Persiapan Penerapan Kurikulum Merdeka Di Mi Al-Ihsan Palembang - Ibrahim Ibrahim; Mita Rolani; Alecia Septiana; Siti Nur Kholifah; Nabila Kontesa (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research discusses the preparation of Madrasah Ibtidaiyah Al-Ihsan Palembang in implementing the Merdeka curriculum. The Merdeka curriculum is an innovative approach to education aimed at providing autonomy to students in their learning. The objective of this research is to understand the methods and approaches used by Madrasah Ibtidaiyah Al-Ihsan in preparing itself to introduce the Merdeka curriculum. We employed a qualitative method in this research. The first step in qualitative research methodology involves observation, interviews, and data collection. Research findings indicate that MI Al-Ihsan has started preparing itself to implement the Merdeka curriculum. This preparation includes teacher training, developing learning materials in line with the curriculum, creating adaptable lesson plans, and discussing difficulties and challenges faced when implementing the Merdeka curriculum, as well as its benefits and drawbacks compared to the previous curriculum. The importance of careful planning before implementing the Merdeka curriculum at MI Al-Ihsan is also emphasized in this article. With thorough planning, this curriculum will maximize the benefits of students' self-development in the future.